(untitled) (Physical Education, Health and Social Sciences, 2025)
Linking professional learning experiences to academic collaborative effectiveness enhances teachers’ capacity to work collectively, share instructional practices, and address academic challenges more effectively. Such experiences also contribute to institutional leadership development by strengthening reflective decision-making, shared leadership, and a culture of continuous improvement within schools. The objectives of the study were to find the level of Professional Learning Experiences, academic collaborative Effectiveness and Institutional Leadership Development, and to find effect and Relationship among Professional Learning Experiences, academic collaborative Effectiveness and Institutional Leadership Development in public sector schools. Quantitative data was collected through numerical methods, primarily using survey questionnaires. The population comprised all male and female elementary school teachers working in Azad Jammu and Kashmir (AJ&K). The research instrument used in the study was a questionnaire. Data was analyzed using both descriptive statistics (mean and standard deviation) and inferential statistics (Pearson correlation and linear regression). Statistical analysis was performed using SPSS software. The study found moderate levels of professional learning experiences, academic collaborative effectiveness, and institutional leadership development among participants. Professional learning experiences were positively and significantly related to both academic collaboration and leadership development, with a stronger impact on collaborative effectiveness. These findings highlight the key role of professional learning in enhancing teachers’ collaboration and leadership capacities. It is recommended that Schools should design continuous and well-structured professional development programs that integrate collaborative activities, reflective exercises, and leadership-oriented tasks. This approach ensures teachers not only acquire knowledge but also apply it through practice and reflection.